The planning of country home grounds - Deibler, Minnie Estella (My University, 1905)
Introduction: The average country man of today, is working toward making this home one of the most pleasant spots on earth for his family and himself. The log cabin on the prairie is changed for a better house with a front lawn; and later, these surroundings do not satisfy the prospering farmer, until the home is again changed into a large, artistic house, with such home grounds as he desires. Observations have proven to us that country home grounds can be improved, and because of the economical and moral values that arise from the influence of well-planned country home grounds, I do not hesitate to say that country home grounds can and should be improved. But too often sad mistakes are made in the planning of thee grounds. Many little corrections in the laying-out of the lot and location, does much toward their artistic improvement.
Citation: Deibler, Minnie Estella. The planning of country home grounds. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Location; Hygenic Conditions; Telford System; Theses; Manuscripts (documents)